Modulation of contraction by intracellular Na+ via Na(+)-Ca2+ exchange in single shark (Squalus acanthias) ventricular myocytes. - Näbauer, M (1992)
1. The effect of direct alteration of intracellular Na+ concentration on contractile properties of whole-cell clamped shark ventricular myocytes was studied using an array of 256 photodiodes to monitor the length of the isolated myocytes. 2. In myocytes dialysed with Na(+)-free solution, the voltage dependence of Ca2+ current (ICa) and contraction were similar and bell shaped. Contractions activated at all voltages were completely suppressed by nifedipine (5 microM), and failed to show significant tonic components, suggesting dependence of the contraction on Ca2+ influx through the L-type Ca2+ channel. 3. In myocytes dialysed with 60 mM Na+, a ICa-dependent and a ICa-independent component of contraction could be identified. The Ca2+ current-dependent component was prominent in voltages between -30 to +10 mV. The ICa-independent contractions were maintained for the duration of depolarization, increased with increasing depolarization between +10 to +100 mV, and were insensitive to nifedipine. 4. In such myocytes, repolarization produced slowly decaying inward tail currents closely related to the time course of relaxation and the degree of shortening prior to repolarization. 5. With 60 mM Na+ in the pipette solution, positive clamp potentials activated decaying outward currents which correlated to the size of contraction. These outward currents appeared to be generated by the Na(+)-Ca(2+)-exchanger since they depended on the presence of intracellular Na+, and were neither suppressed by nifedipine nor by K+ channel blockers. 6. The results suggest that in shark (Squalus acanthias) ventricular myocytes, which lack functionally relevant Ca2+ release pools, both Ca2+ channel and the Na(+)-Ca2+ exchanger deliver sufficient Ca2+ to activate contraction, though the effectiveness of the latter mechanism was highly dependent on the [Na+]i.